Acyclic cucurbit[n]uril-type containers as receptors for neuromuscular blocking agents : structure-binding affinity relationships - Shaya, David (Array, 2019)
Acyclic cucurbit[n]uril molecular containers 1 and 2C3 have previously been shown to strongly bind to the neuromuscular blocking agents rocuronium, vecuronium, pancuronium, and cisatracurium in vitro by optical methods and to reverse neuromuscular block in vivo in rats. In this paper we study the in vitro binding of a panel of acyclic CB[n]-type receptors toward the four neuromuscular blocking agents and acetylcholine to develop structure-binding affinity relationships. The selected variants include those with different aromatic sidewalls (e.g. 1Me4 with dimethyl o-xylylene walls; 3 with 1,8-linked naphthalene walls), with different glycoluril oligomer lengths (e.g. 4 and 5 based on glycoluril trimer), and with different linker lengths between aromatic wall and SO3- solubilizing group (e.g. 2C2–2C4). Based on the analysis of complexation induced changes in 1H NMR chemical shift we conclude that the hydrophobic regions of the guests bind in the hydrophobic cavity of the hosts with the cationic moieties of the guest binding at the ureidyl C=O portals by ion-dipole and ion-ion interactions. The thermodynamic parameters of binding were determined by direct and competition isothermal titration calorimetry experiments. We find that hosts 4 and 5 based on glycoluril trimer form significantly weaker complexes with the streroidal NMBAs than with the analogues hosts based on glycoluril tetramer (1 and 2C3). Similarly, hosts 1Me4 and 3 with different length and height aromatic walls do not exhibit the extreme binding constants displayed by 2C3 but rather behave similarly to 1. Finally, we find that hosts 2C2 and 2C4 bind only slightly more weakly to the NMBAs than 2C3, but retain the ability to discriminate against acetylcholine, and possess higher inherent water solubility than 2C3. Host 2C4, in particular, holds potential for future in vivo applications.